Modelling the spatial patterning of the primordia in the lower jaw of alligator mississippiensis - Kulesa, P; Cruywagen, G; Lubkin, S; Maini, P; Sneyd, J; Murray, J (1995)
We propose a model mechanism for the initiation and spatial positioning of teeth primordia in the alligator, Alligator mississippiensis. Detailed embryological studies12–14 have shown that jaw growth plays a crucial role in the developmental patterning of the tooth initiation process. The development of the spatial pattern occurs on a timescale comparable to jaw growth. Based on biological data we develop a dynamic patterning mechanism, which crucially includes domain growth. The mechanism can reproduce the spatial pattern development of the first seven teeth primordia in the lower jaw of A. mississippiensis. The results for the precise spatio-temporal sequence compare well with experiment.